Research on MEC traffic offloading scheme in 5G smart campus business scenarios - Ling LI; Hua WANG (Dianxin kexue)
MEC (multi-access edge computing) is one of the key technologies of 5G.Through the integration of communication and computing technologies, service localization and close deployment can be realized.At present, 5G smart campus has spawned many new application scenarios.The key step to construct the 5G smart campus is how to offload user data to the MEC platform to realize the deep integration of technology and business.Firstly, the overall architecture of 5G smart campus was introduced.Then, three traffic offloading technologies and their advantages and disadvantages were expounded.Finally, the scheme selection of traffic offloading in campus resource visits, access to electronic resources, smart education and campus security monitoring was discussed.It is expected to provide theoretical support for the upcoming construction of 5G smart campus.